Teaching interpretation in singing / Puteri Najiha Mustafa - Mustafa, Puteri Najiha (2019)
The purpose of this study is to investigate how voice teachers define interpretation and how they teach their student's interpretation. In this research, three experienced vocal lecturers from the Faculty of Music were selected based on their qualifications and their background as well as experience in teaching voice students at the UiTM Faculty of Music. The method for this study is qualitative and data collected using the interview method. Semi-structured interviews with a set_ of core questions were prepared. In my findingj all voice teachers said that interpretation is expression and feeling in the piece of music which singers sing and convey the message to the audience through the phrasings, dynamics, emotion, facial expression, and body gestures help the singers to express the emotion according to the message or story in each song. They also agreed that there are no differences in interpretation between art songs and arias. The most important is the understanding of the story or message through the lyrics and how it is delivered to the audience.